Evaluating Student Satisfaction and Knowledge Transfer in Synchronous Online University Extension Courses after the Pandemic - Morales Zúñiga, Laura (2025)
This study aims to assess the overall satisfaction and perceived effectiveness of  knowledge transfer in synchronous online courses delivered through  post-pandemic university extension programs. The study employed a quantitative methodological design that entailed distribution of a questionnaire among 190 students enrolled in a teaching extension program at the University of Costa Rica. Data was analyzed through the Partial Least Squares Structural Equation Modeling (PLS-SEM) method and SmartPLS software. The results show that there is a robust correlation between knowledge transfer and overall satisfaction, emphasizing that teacher responsiveness significantly influences student satisfaction.